279 Development, selection criteria, and performance of Composite IV sheep at the U.S. Meat Animal Research Center. (30th November 2020) - Murphy, Tom; Freking, Brad; Bennett, Gary L; Keele, John W
Abstract: Average ewe prolificacy is low across the U.S., while fixed and variable costs of production can be substantial, especially in traditional shed-lambing systems. Pasture-lambing can reduce input costs but can present greater risk of inclement weather, predation, and internal parasitism. The Composite IV is a ½ Romanov, ¼ Katahdin, and ¼ White Dorper hair sheep developed at the U.S. Meat Animal Research Center. Objectives were to summarize Composite IV ewe and lamb performance under a pasture-lambing system with minimal disruption through weaning. Lamb survival to and body weight at weaning were greatest for singles (0.90 and 19.9 kg, respectively), intermediate for twins (0.82 and 15.9 kg), and lowest for triplets (0.65 and 14.6 kg; P < 0.01). Number of lambs born and weaned per ewe lambing were lower at 1-yr of age (1.55 and 1.24, respectively) than at 3- to 5-yr of age (2.20 to 2.23 and 1.75 to 1.82; P < 0.01). Within mature ewes (2- to 5-yr-old), twin litters were most frequent (58.7%), triplets intermediate (24.7%), and singles least (16.6%). While number of lambs weaned and total litter weaning weight were greater for triplet- than twin-bearing ewes (2.06 vs 1.70 and 28.9 vs 26.0 kg, respectively; P < 0.01), triplet-bearing ewes lost 1.78 lambs per additional lamb weaned. Results suggest productivity in pasture-lambing systems can be enhanced by identifying complementary breed combinations, maintaining heterosis, and selecting for characteristics associated with reduced labor and enhanced well-being.